Optimizing photocatalytic degradation of methyl violet dye in a recirculating slurry-type reactor - F. Shokry; M. El-Gedawy; S.A. Nosier; M.H. Abdel-Aziz (Results in Chemistry)
This study examined the photocatalytic degradation of wastewater containing methyl violet dye in a recirculating slurry-type reactor using commercial TiO2 as the photocatalyst under ultraviolet irradiation. The effects of initial dye concentration (10 – 80 ppm), photocatalyst dosage (0.2 – 1 g/L), solution pH (2 – 11), and flow rate (2 – 4 L/min) on degradation efficiency were thoroughly assessed. Results showed that degradation efficiency increased with pH, peaking at neutral pH (7), before declining at higher values. Similarly, catalyst loading up to 1 g/L enhanced efficiency, but further increases caused a decline. Higher solution flow rates improved mass transfer by increasing turbulence, leading to enhanced degradation efficiency. Optimal conditions (neutral pH, 1 g/L catalyst loading, and 4 L/min flow rate) achieved complete decolorization of a 10-ppm dye solution. These findings highlight the feasibility of achieving high degradation efficiencies under practical conditions, supporting the potential for industrial-scale application in effluent treatment.